Interplay between potassium doping and bandgap profiling in selenized Cu(In, Ga)Se2 solar cells: A functional CuGa:KF surface precursor layer. (May 2018) - Cai, Chung-Hao; Chen, Rong-Zhi; Chan, Ting-Shan; Lu, Ying-Rui; Huang, Wei-Chih; Yen, Chao-Chun; Zhao, Kejie; Lo, Yu-Chieh; Lai, Chih-Huang
Abstract: The progress of selenized Cu(In, Ga)Se2 (CIGSe) solar cells is limited by low open-circuit voltage (Voc), which results from the Ga-deficient surface and undesirable bandgap profile after selenization. Controlling the Ga grading, especially on the CIGSe surface, is challenging but critical for further efficiency improvement. Here, the simple sputtering route with K incorporation is presented to engineer single- or double-graded bandgap. The K incorporation through sputtered precursors can considerably affect the Ga profile in CIGSe during selenization, essentially distinct from reported KF post-deposition treatment, in which the Ga profile keeps unchanged. Using synchrotron-based X-ray absorption spectroscopy and first-principle calculations, we verify that Ga diffusion via Cu vacancies is restrained due to the presence of KCu defects. Therefore, by introducing a CuGa:KF surface layer on the bi-layer precursors, the surface Ga content of CIGSe is increased effectively, achieving a notch-like Ga distribution after selenization. This unique CuGa:KF layer significantly boosts the Voc and yields over 15% efficiency, even with a low reactive Se vapor for selenization. Our approach, completely compatible with the existing fabrication process, offers a new direction for engineering band structure without sulfurization. Graphical abstract: fx1 Highlights: The double Ga-grading in CIGSe absorber can be achieved by simple selenization with K-incorporated precursors. The route for incorporating K via sputtering well suitable for industrial purposes is proposed. Modulation of K distribution can tailor the Ga profile due to presence of KCu defects verified by EXAFS. The first-principle calculations show that the presence of KCu defects alters Ga migration. The surface CuGa:KF layer increases the surface Ga content, leading to the boosted Voc and over 15% efficiency.